Cover Image, Volume 32, Issue 9. (13th August 2019) - Zaiss, Moritz; Anemone, Annasofia; Goerke, Steffen; Longo, Dario Livio; Herz, Kai; Pohmann, Rolf; Aime, Silvio; Rivlin, Michal; Navon, Gil; Golay, Xavier; Scheffler, Klaus
Abstract : The cover image is based on the RESEARCH ARTICLE Quantification of hydroxyl exchange of D‐Glucose at physiological conditions for optimization of glucoCEST MRI at 3, 7 and 9.4 Tesla by Moritz Zaiss et al., https://doi.org/10.1002/nbm.4113 .